The Impact of Digital Marketing Innovation on Customer Engagement With Brands: A Case Study of the Iraqi Telecommunications Sector - Zaid Ghazi Majdi Badiri (Research Parks Publishers, 2026)
The current research aims to identify the impact of innovation in digital marketing across its dimensions (digital attraction, digital interaction, digital retention, digital learning, and digital communication) on customer interaction with the brand (informational interaction and social interaction). This is an applied study in the Iraqi telecommunications sector, where the research sample consisted of (163) employees in telecommunications companies in Baghdad Governorate. The research problem was represented by the main question: (What is the impact of innovation in digital marketing on customer interaction with the brand in the Iraqi telecommunications sector?) The descriptive analytical method was used to achieve the research objectives and develop its instruments, using the statistical programs (AMOS.V.29 and SPSS.V.29). The research results showed a significant positive relationship between the level of innovation in digital marketing and customer interaction with the brand in the Iraqi telecommunications sector, indicating that adopting innovative digital methods contributes to enhancing customer interest and participation.